Determinants of Profit Growth - Emylia Andriani; Erma Setyawati (International Journal of Economics Development Research (IJEDR), 2023)
The objective of this research is to analyze the influence of Current Ratio, Current Liability to Inventory, Total Assets Turnover, Net Profit Margin, Sales Growth, and Company Size on profit growth, focusing on the consumer goods industry sector companies listed on the Indonesian Stock Exchange from 2018 to 2022. This study utilizes secondary data from a population of 30 companies within the consumer goods industry sector listed on the Indonesian Stock Exchange during the specified period. Purposive sampling technique is employed alongside the multiple linear regression analysis method. The findings indicate that, individually, Current Liability to Inventory and Net Profit Margin do not significantly affect the profit growth of the 30 companies in the consumer goods industry sector listed on the Indonesian Stock Exchange from 2018 to 2022. However, Current Ratio, Total Asset Turnover, Sales Growth, and Company Size demonstrate significant effects on the profit growth of these companies during the same period.